Draw me a picture, tell me a story: Evoking memory and supporting analysis through pre-interview drawing activities - Ellis, Julia; Hetherington, Randy; Lovell, Meridith; McConaghy, Janet; Viczko, Melody (Alberta Journal of Educational Research, 2013)
In interviews for interpretive inquiry or interpretive case studies, researchers hope to grasp participants’ perspectives and learn about the nature and meaning of their experiences. There are many challenges or requirements for useful or successful interviews. In this paper we identify important aspects of interviews and examine the helpful contributions of using pre-interview activities. Pre-interview activities were drawings or diagrams that participants completed about the experiences of interest. Participants brought the completed drawings to their interviews and the interviews commenced with presentation and discussion of these visuals. This paper presents four studies that illustrate how the use of pre-interview activities can support participants in identifying central ideas in their experiences. In the interviews, the participants spoke at length about the visual representations they produced and in these reflections they identified central ideas or key themes in the experiences. Some drawings were a source of visual metaphors for discussing the experience and some highlighted whole-part relationships that informed interpretation. The findings contribute to conversations about how to “invite stories” rather than “request reports” from participants, how images other than photographs can serve as evocative and potent visuals to support memory and reflection in interviews, and how researchers can better or more directly access a participant’s meaning. Lors d’entrevues dans le contexte d’enquêtes interprétatives ou d’études de cas interprétatives, les chercheurs espèrent comprendre les perspectives des participants et de se renseigner sur la nature et le sens de leurs expériences. Les entrevues utiles ou réussies impliquent de nombreux défis et plusieurs exigences. Dans cet article, nous identifions certains aspects importants d’entrevues et examinons les contributions utiles des activités pré-entrevues. Les activités pré-entrevues consistaient en des dessins ou des diagrammes complétés par les participants et portant sur des expériences qui les intéressaient. Les participants sont arrivés aux entrevues avec leurs dessins terminés; les entrevues ont débuté par une présentation et une discussion de ces illustrations. Cet article présente quatre études qui illustrent la mesure dans laquelle l’emploi d’activités pré-entrevues peut appuyer les participants dans l’identification des idées qui sont centrales à leurs expériences. Lors des entrevues, les participants ont longuement parlé au sujet des représentations visuelles qu’ils avaient produites; au cours de leurs réflexions, ils ont identifié les idées centrales, ou thèmes clés, de ces expériences. Certains dessins étaient sources de métaphores visuelles servant d’appui à l’expérience; d’autres mettaient l’accent sur les relations partie-tout qui éclairaient leurs interprétations. Les résultats viennent contribuer aux conversations sur la façon d‘inviter les participants à « raconter des histoires » plutôt que de leur « demander des rapports », sur le rôle que peuvent jouer les images (autres que les photos) comme illustrations évocatrices et puissantes qui appuient la mémoire et la réflexion lors d’entrevues, et sur les moyens pour les chercheurs d’avoir un meilleur accès, ou un accès plus directe, au sens que veulent communiquer les participants.